Gandhi - Attenborough, Richard; Briley, John; Kingsley, Ben; Bergen, Candice, 1946-; Fox, Edward, 1937-; Gielgud, John, 1904-2000; Howard, Trevor, 1916-1988; Mills, John, 1908-2005; Sheen, Martin; Williams, Billy; Taylor, Ronnie; Shankar, Ravi, 1920-2012; et al. (Columbia TriStar Home Video, 2001)
Tells the story of Gandhi's adult life, when he led an entire country to freedom, using non-violent methods.